Developing a slow city tourism evaluation index: a Delphi-AHP review of Cittaslow requirements. Issue 4 (3rd April 2022) - Kim, Jeong Hyun; King, Brian E. M.; Kim, Seongseop (Sam)
Abstract: This study proposes and verifies the slow city tourism evaluation index (SCTEI). SCTEI offers scholars and practitioners the capacity to assess the attractiveness and/or performance of slow cities in the context of sustainable tourism. The study participants consisted of a panel of slow city and sustainable development experts. These professionals were engaged in a Delphi-analytic hierarchy process for the purposes of scale development and verification. Four rounds of surveying were conducted and generated a multi-dimensional structure, consisting of seven domains, 18 subdomains, and 60 items. Locality, conviviality, and education were outstanding amongst the seven domains. The newly developed SCTEI provides practical guidelines for ascertaining a slow city's sustainable tourism performance and offers a standardized instrument for comparison and benchmarking purposes.